Improvement waktu pelayanan pasien bagian ultrasonografi dengan metode lean di RSUP Prof dr. R.D Kandou - Indra Tjen; T.M.A. Ari Samadhi; Ronald Rachmadi (Widya Teknik, 2017)
Patient care process for the ultrasound section starting from the registration of patients and will be conducted further examination schedule patient and the patient will perform an ultrasound process according a predetermined time. Based on the observations made, in the process of scheduling a patient to wait long to turn the examination, this is because the number of patients that a lot of time and service time, so the capacity of patient care on average per day is 8 people with the time of service with service time 47 minutes / people . By using Lean with VALSAT (value stream mapping analysis tools) to identify waste that does not provide added value (non-value added activity), the type of waste that often occurs is waiting and overproduction. Furthermore, the fishbone diagram sought the cause of waste that is then given to the proposal in the form of recommendations to the party responsible for such repairs SOP and supervision at each ultrasound process. Based on the minimization of waste the time of patient care becomes 31.28 minutes / person. By the time the patient care capacity increased to 11 people / day.